Novel external cooling solution for electric vehicle battery pack - Kawtar Benabdelaziz; Badreddine Lebrouhi; Anas Maftah; Mohammed Maaroufi (Energy Reports, 2020)
The future use of electric vehicles in the southern regions of the world could face several problematics related to high temperature, mostly when charging at high power. This paper proposes a new external cooling solution for cooling EV batteries pack at higher temperature conditions especially for those without effective cooling system embedded. A 3D-thermal model has been developed in order to investigate and to analyse the temperature distribution over the battery pack, the ANSYS FLUENT software has been used to solve the model development. Furthermore, different external cooling solutions have been proposed by using the engineering process design to study their impact on the internal temperature of the battery pack.
Keywords: 330; Thermal model; Batteries; Electric vehicle; Finite volume method; Response surface method; ANSYS FLUENT